One-Pot Synthesis of Benzo[g]indazoles via Suzuki–Miyaura Coupling and Aldol Condensation Cascade Reaction - Ko, Hye Seung; Jeoung, Re Gin; Kang, Nam Sook; Heo, Jung-Nyoung (Synthesis, 2025)
A highly efficient one-pot synthesis of benzo[g]indazole derivatives has been achieved through a cascade Suzuki–Miyaura coupling and aldol condensation reaction. Using Pd(OAc)2 and S-Phos as the catalytic system, the reaction delivered excellent yields and showed broad tolerance for various substituents on 2-formylphenylboronic acids. Moreover, this method was successfully applied to the synthesis of benzo[g]indazole-5-carbonitrile and pyrazolo[4,3-h]quinoline-5-carbonitrile derivatives by altering the coupling partners. This versatile protocol offers a straightforward and effective method for synthesizing biologically significant heterocyclic compounds.
Keywords: benzo[g]indazoles; Suzuki–Miyaura coupling; aldol condensation; one-pot reaction; 2-formylphenylboronic acids; pyrazolo[4,3-h]quinoline